Italian Police Seize $1 Million Worth of Antiquities From Roman Businessmen - Naomi Rea (Les Carnets de l’ACoSt)
An article in artnet News published on May 14, 2018, details the seizure of Roman antiquities in Lazio that included several figurative terracottas, including two animal heads of monumental size. These are related to the recent surge of illegal antiquities sales that take place on-line through Facebook, Ebay, and Amazon, among other portals.